Enterprise Surveys : Colombia Country Profile 2017 - World Bank (World Bank, Washington, DC, 2018)
The Enterprise Surveys (ES) focus on many aspects of the business environment. These factors can be accommodating or constraining for firms and play an important role in whether an economy’s private sector will thrive or not. An accommodating business environment is one that encourages firms to operate efficiently. Such conditions strengthen incentives for firms to innovate and to increase productivity, key factors for sustainable development. A more productive private sector, in turn, expands employment and contributes taxes necessary for public investment in health, education, and other services. Questions contained in the ES aim at covering most of the topics mentioned above. The topics include infrastructure, trade, finance, regulations, taxes and business licensing, corruption, crime and informality, access to finance, innovation, labor, and perceptions about obstacles to doing business. This document summarizes the results of the Enterprise Survey for Colombia. Business owners and top managers in 993 firms were interviewed between June 2017 and June 2018. Figure 2 provides a description of the sample breakdown across the three survey design categories: business sector, firm size, and location.